Infection of Drosophila melanogaster by Tubulinosema kingi: stage-specific susceptibility and within-host proliferation. - Vijendravarma, R; Godfray, H; Kraaijeveld, A (2008)
Despite its importance as a model organism very little is known about the interaction between Drosophila and its microsporidian pathogens. Here we report on the relative susceptibility of Drosophila melanogaster life history stages to infection by Tubulinosema kingi, and on patterns of pathogen proliferation. We find that only larvae can be infected, and that this susceptibility decreases with larval age. Following infection, the pathogen shows little subsequent proliferation in larvae, a limited amount in pupae while it replicates greatly in adults. We present evidence that the host launches a cellular immune response after infection with the pathogen, although its effectiveness remains to be demonstrated.